NUTRITIONAL DEFICIENCY ANEMIA IN YOUNGERS AND PREGNANT WOMEN (World Journal of Current Medical and Pharmaceutical Research, 2019)
Introduction: Anemia was global health problem. It was highly prominent in India was caused by nutritional deficiency in younger individuals due to lack knowledge on diet. Methods and materials: This study performed in Sri Venkateswara college of Pharmacy, Etcherla, Srikakulam. And RIMS Hospital, Srikakulam. Study performed based on cohort study. Data was collected from student’s blood samples tested by using Sahlisehematometer manual method. Recorded data from hospital regarding pregnant women. Result: Total 300 samples was collected in that 100 student samples, 50 Pregnant women total 150 samples was effected with anemia in that younger female students was highly 16% anemic 9-9.9 Hb%, In males 28% lower anemic than females and also Hb% 12- 12.9 is higher than females. Discussion: In our study younger females were highly affected by anemia same as author study reported but they saying lack of knowledge on diet was leads to the Anemia. Authors in those study in Pregnant women 15-20 aged more women affected with anemia but in our study saying 21-25 years ages more women was affected by anemia. Conclusion: In our study highly females were affected with anemia due to lack of knowledge on diet, economical, social problem and more over now a day’s food habit life style.